PENCEMARAN BTEX DAN LOGAM BERAT PADA HUTAN MANGROVE PESISIR TAMBAK LEKOK - Edyson Indawan (Bumi Lestari Journal of Environment, 2009)
This research was aimed to explore land function changes and contamination levels (BTEX and heavy metals) on the mangrove area. The results of BTEX parameters from soil sample and indentified benzene showed heavy metal contaminations on Plot A, B, C and D were16.30 ppm, 81.30 ppm, 56.90 ppm, and 93.50 ppm respectively, but it was not detected on Plot E. Toluene contaminations was 481 ppm, 824 ppm, 490 ppm, 896 ppm, and 93.50 ppm. It showed that Plot B and D were heavily contaminated. Based on EC values of water, it showed that contamination was heavy on Plot B (4.76 us/cm), Plot C (4.67 us/cm), Plot D (4.64 us/cm) and Plot E (4.66 us/cm). Based on water samples and detected benzene, it indicated an heavy contamination on Plot A (24.30 ppm), Plot B (8.13 ppm), Plot C (20.20 ppm), Plot D (8.13 ppm), Plot E (8.13 ppm), while toluene (460 ppm, 522 ppm, 509 ppm, 319 ppm, 522 ppm) contaminated slightly. Ethylbenzene and Xilene were not detected by gas chromatography. EC value of soil showed that intensive contamination occurred on Plot E (4.81 us/cm). It showed that intensive contamination took place on soil mainly by Pb contamination on Plot C, Plot D, and Plot E (5.98 mg/kg, 7.24 mg/kg, and 6.43 mg/kg). Meanwhile, Plot A and B were slightly contaminated only. The same levels occurred on Cu for all plots, except Plot A (6.22 mg/kg). Zn and Cr did not contaminate, while Ag and Cd were not detected. Water medium was not contaminated by Pb, Cd, Cr, and Zn. Furthermore, Ag and Cu were not detected.